Sexual segregation in red deer: is social behaviour more important than habitat preferences? - Alves, Joana (2018)
Sexual segregation among vertebrates is a common phenomenon, usually assumed to be associated with sexual body size dimorphism and explained by differences in habitat use or social behaviours. Various hypotheses explain sexual segregation in terms of social or habitat factors. The factors controlling sexual segregation are as yet unclear and the hypotheses put forward to explain it have generated contradictory results, indicating that different mechanisms can be involved. We analysed the three components of sexual segregation (i.e. social, spatial and habitat) in a red deer, Cervus elaphus, population of a Mediterranean-type mountainous environment. We also examined age- and offspring-related segregation. Aiming to understand the role of social interactions and habitat preferences for red deer segregation, we used 5 years of direct observations of animals. Adult males and sexually active females showed complete segregation during the year except in the rut and autumn seasons, showing that a red deer tends to be aggregated with its peers outside the reproductive period. The results suggested that red deer segregated not only by sex, but also between age classes, indicating that sexual segregation hypotheses need to explain more than differences between sexes. Furthermore, both social behaviour and habitat preferences contributed significantly to sexual segregation, indicating that this phenomenon results from different choices made by males and females with respect to security and food availability in their living areas and dissimilar social behaviour of different sexes and age classes.